Distinct Functions of Autoantibodies Against Interferon in Systemic Lupus Erythematosus: A Comprehensive Analysis of Anticytokine Autoantibodies in Common Rheumatic Diseases. Issue 7 (July 2016) - Gupta, Sarthak; Tatouli, Ioanna P.; Rosen, Lindsey B.; Hasni, Sarfaraz; Alevizos, Ilias; Manna, Zerai G.; Rivera, Juan; Jiang, Chao; Siegel, Richard M.; Holland, Steven M.; Moutsopoulos, Haralampos M.; Browne, Sarah K.
Abstract : Objective: Anticytokine autoantibodies occur across a range of hematologic, pulmonary, and infectious diseases. However, systematic investigation of their presence and significance in autoimmune diseases is lacking. This study was undertaken to examine the distinct functions of anticytokine autoantibodies in patients with systemic lupus erythematosus (SLE) compared to patients with other rheumatic diseases and healthy controls. Methods: Serum samples from patients with SLE (n = 199), patients with primary Sjögren's syndrome (SS) (n = 150), patients with rheumatoid arthritis (RA) (n = 149), and healthy controls (n = 200) were screened for 24 anticytokine autoantibodies using a multiplex bead‐based assay. To evaluate the biologic activity of anticytokine autoantibodies, their ability to block cytokine‐induced signal transduction or protein expression was measured. RNA sequencing was performed on whole blood in a subset of healthy controls and patients with SLE. Results: Patients with SLE and those with SS had a striking excess of autoantibodies against interferons and the interferon‐responsive chemokine interferon‐inducible protein 10 (IP‐10). Only autoantibodies against type I interferon, interleukin‐12 (IL‐12), and IL‐22 exhibited neutralizing activity. In SLE, the presence of anti–interferon‐γ autoantibodies was correlated with more severe disease activity, higher levels of anti–double‐stranded DNA antibodies, and elevated expression of interferon‐α/β–inducible genes. Conversely, in SLE patients with blocking anti–interferon‐α autoantibodies, the type I interferon gene expression signature was normalized. Anti–type III interferon autoantibodies (λ2, λ3) and anti–IP‐10 autoantibodies were newly recognized in SLE patient serum, and autoantibodies against macrophage‐colony stimulating factor, IL‐4, IL‐7, IL‐17, and IL‐22, none of which have been previously identified in rheumatic conditions, were discovered. Conclusion: Anticytokine autoantibodies are associated with distinct patterns of disease in SLE, SS, and RA. Anti‐interferon autoantibodies are overrepresented in patients with SLE and those with SS, and fall into distinct functional classes, with only a subset of anti–type I interferon antibodies exhibiting neutralizing activity. Anti–interferon‐γ autoantibodies are correlated with increased disease activity and interferon‐related gene expression, suggesting that such autoantibodies may contribute to the pathogenesis of SLE.